Structural behaviour of composite floor systems under column removal scenario - Fu, Qiuni (2018)
In this study, four 3D composite floor specimens were quasi-statically tested to failure under an internal column removal scenario. Two principal objectives were achieved, viz. unveiling the load-resisting mechanisms (Alternate Load Paths) in 3D composite floor systems and reveal of effects from slab aspect ratio, degree of composite action and boundary condition. Besides, numerical models were employed to study inter-dependence among load-resisting mechanisms in 3D composite floor systems. It is found that dominant flexure would suppress the development of CA, since they are the two complimentary components in the double-span beams above the missing column. The slab contribution at the final stage involves TMA remains constant if steel reinforcement, profiled decking and dimensions of the slab are the same. Furthermore, the verified modelling method was applied to a full-scale 3D composite floor system subjected to sudden column loss, yielding the dynamic behaviour. Last but not least, a mechanical model was proposed to estimate the entire load-deflection response of 3D composite floor systems subjected to an internal column loss. Compared with actual test results and numerical simulations, the model shows reasonable accuracy. Besides, the model can capture the effects of key parameters, such as slab aspect ratio, joint type, number of joint bolts, slab thickness, reinforcement ratio in the slab and thickness of steel decking. Most importantly, the procedure of the model can be implemented by a spreadsheet method, which provides a simple and numerical robust tool for engineers to calculate progressive collapse resistance of structures for a missing column scenario.